Komposisi Vegetasi, Keanekaragaman Jenis, Dan Pola Dispersi Tumbuhan Langka Pada Kawasan Laboratorium Alam Lahan Gambut Universitas Palangka Raya: The composition of vegetation, species diversity, and dispersion patterns of rare plants in the Natural Peatland Laboratory Area of the University of Palangka Raya - Setiarno, Setiarno; Nababan, Suzet Rotua Tasya; Hidayat, Nisfiatul; Rotinsulu, Johanna Maria; Junaedi, Ajun (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2025)
This research aims to describe and analyze species composition, species diversity, and dispersion patterns of rare plants, particularly those classified as critically endangered, in the Natural Laboratory of Peatland Palangka Raya University. Vegetation data collection was conducted using the quadrat plot technique based on a purposive systematic sampling. The data in the research plots were analyzed using Microsoft Excel, referring to the Important Value Index (IVI), species dominance index, diversity index, evenness index, and dispersion index. This research identified 47 types of plants (the total number of plants at the seedling, sapling, pole, and tree levels) categorized into 38 genera and 27 families. There were rare plants fall into critically endangered or endangered, namely ramin (Gonystylus bancanus) and nyatoh (Palaquium bintuluense). Nyatoh (Palaquium bintuluense), jambu-jambu (Eugenia spp.), and mangkinang (Elaeocarpus stipularis BI.) were almost always among the top five dominant species from the seedling stage to the tree stage at various peat thickness levels, but there was no concentration of species dominance in the plot. The majority of the species diversity index values (Shannon-Wiener) in the plots were classified as high (H’>3), indicating that the forest ecosystem conditions at the location are relatively stable. The evenness index of species in all plant communities and peat thickness levels fell into almost uniform abundance category (E = 0.76 – 0.95). The dispersion pattern of the population of critically endangered rare plants, such as Gonystylus bancanus (Mig.) and Palquium bintulense, at various peat thickness levels was clustered. In terms of growth stages, the population of Palquium bintulense was entirely clustered, while that of Gonystylus bancanus (Mig.) was only clustered at the sapling stage, but at the seedling and pole stages, it had random pattern.